Albert Camus - Hughes, Edward J. 1953- (Critical lives, 2015)
One of France's most high-profile writers and a Nobel Prize-winner, Albert Camus experienced both public adulation and acrimonious rejection during his career, which was cut short by a fatal car accident in 1960. His novels The Outsider and The Plague earned him a reputation as a writer who captured the mood of the age. Edward J. Hughes unravels the life of a complex personality whose work and stance were the subjects of intense interest and scrutiny. 'I do not guide anyone', Camus pleaded in his last interview, reinforcing the paradox of a leading figure who in private wrestled with the challenge of pursuing his craft as a writer in an age of pressing ideological conflict."--